Investigation of rubber waste in self-compacting concrete during hardening and its performance in the civil and environmental industry (Journal of Civil Engineering Researchers, 2017)
In order to used and worn out tires and a better understanding of the commercial potential of used tires as rock molders in the concrete industry and the performance of this type of concrete in structural and non-structural applications, the study of the properties of new and complex concrete has to be necessary to contain these lesions. Testing fresh concrete such as slump, since reaching a diameter of 50 cm (T50) Hopper V, Box L, ring J and hardened concrete include compressive strength on samples cube 28 and 56 days to dimensions of 10 x 10 cm and bending strength on samples prismatic dimensions of 75 x 15 x 15 cm by 28 days were done. In this research, used tires, as in the 5 designs mixed with 0, 5, 10, 15 and 20 percent replacement of coarse aggregate were used for the volume. Results showed that by increasing the amount of gum paste viscosity and increase the ability to pass, dispersion and filling, reduced. The compressive and flexural strength of the samples also decreased with increasing rubber content, the lowest drop, at 5%, and the highest drop in the 20% rubber replacement compared to the control plan, and we are witnessing with dropped by 5% and 20% in the maximum and minimum in the replacement.
Keywords: self-compacting concrete; rubber; fresh concrete; flexural strength; compressive strength; environment; tensile stress